Pandangan al-H{a>fiz} Shiha>b al-Din al-Bus}i>ri Terhadap Hadis Zawa>id Dalam Kitab Mis}ba>h} az-Zuja>jah fi> Zawa>id Ibn Ma>jah - Verawati, Sellyana; Muhid; Andris Nurita; Alda Nihayatul Arifah (Farabi, 2024)
This research is a study of the views of al-Hafiz Shihab al-Din Al Busiri view of the zawaid Hadith, in his book al-Busiri examines the zawaidtraditions in the book of Ibn Majah. The zawaid hadith contained in Sunan Ibn Majah has a lot of debate among hadith scholars, many differences of opinion are found in the legal status and number of zawaid hadith contained in Sunan Ibn Majah. In the book Misbah az-Zujajah fii Zawaid, al-Busiri tries to provide an assessment of zawaid traditions and the number of zawaid traditions found by al-Busiri. However, the calculation has some differences in calculation among hadith scholars, therefore this needs to be known and studied. This research uses qualitative research methods that are descriptive interpretative, this research is a type of library research by collecting data through various literatures which are then described objectively. The main reference source of this research is the book Misbah az-Zujajah fii Zawaid Ibn Majah, while supporting sources are reference books, books, journal articles and other literature related to this research. From the findings it is stated that according to al-Busirithe zawaid traditions amount to 1552 Hadith and not all these Hadith are da'if, some are sahih, hasan, or dhaif. In writing the book Misbah az-Zujajah fii Zawaid, al-Busiri used various methods to determine the validity of the zawaid tradition.